THE INFLUENCE OF ISLAMIC CORPORATE GOVERNANCE AND PROFIT MANAGEMENT ON COMPANY VALUE IN SHARIA COMMERCIAL BANKS FOR THE 2018-2021 PERIOD - Safitri, Desiana; Hanif, Hanif; Kurniawan, Agus; Audia, Nanda (Robust: Research of Business and Economics Studies, 2024)
Company value is investors' perception of the company which is often linked to share prices. The growth of Islamic banking is increasing, the implementation of Islamic Corporate Governance (ICG) has become an obligation. ICG implementation aims to overcome the emergence of various risks and problems. Apart from these goals, ICG is also the main focus for making banking superior and highly competitive. The results in this study indicate that Islamic corporate governance has a positive effect on firm value, and earnings management has a positive effect on firm value. The conclusion in this study is H1 which states that Islamic corporate governance has a negative and significant effect on accepted firm value and H2 states that earnings management has a positive and significant effect on accepted firm value and H3 which states simultaneously that both variables, namely Islamic corporate governance and earnings management can have an effect to accepted firm value.